Evaluation of dynamic contrast-enhanced MRI derived microvascular permeability in recurrent glioblastoma treated with bevacizumab - Vollmuth, Philipp; Wiestler, Benedikt; Graf, Markus; Heiland, Sabine; Schlemmer, Heinz-Peter; Wick, Wolfgang; Wick, Antje; Bendszus, Martin; Radbruch, Alexander (Journal of neuro-oncology, 2015)
Bevacizumab, an antibody to vascular endothelial growth factor, is commonly used in the setting of recurrent glioblastoma (rGB). The aim of the present study was to evaluate whether dynamic-contrast-enhanced MRI (DCE-MRI) derived microvascular permeability is related to bevacizumab treatment outcome in rGB. Twenty-two patients with rGB underwent DCE-MRI at a median of 2.6 weeks prior initializing bevacizumab therapy. Follow-up MRI-scans (DCE-MRI available for 19/22 patients) were obtained after a median of 9.9 weeks. The volume transfer constant (Ktrans)—an estimate related to microvascular permeability—at baseline and voxel-wise-reduction (VWR) in Ktrans at first follow-up were measured from the entire contrast-enhancing tumor (CET) and correlated with progression-free and overall survival (PFS, OS) using uni- and multivariate cox-regression (significance-level p < 0.05). Baseline Ktrans ranged from 0.050 to 0.205 min−1 (median, 0.109 min−1). The VWR in Ktrans ranged from 19.9 to 97.2 % (median, 89.4 %). Patients with lower baseline Ktrans and higher VWR in Ktrans showed significantly longer PFS and OS. Given the strong correlation of VWR in Ktrans and CET-volume changes (Spearman’s ρ = −0.73, p < 0.01) both variables were included in a multivariate model. Thereby, neither VWR in Ktrans nor CET-volume changes retained independent significance for PFS or OS. Pre-treatment Ktrans stratifies PFS and OS in patients with bevacizumab-treated rGB. Although early pharmacodynamics changes in Ktrans were not assessed, the VWR in Ktrans at first follow-up had no additional benefit over assessment of CET-volume changes. Further prospective trials are needed to confirm these findings and to elucidate the potential role of pre-treatment Ktrans as a predictive and/or prognostic biomarker.
Published online: 31 October 2014
Gesehen am 29.06.2020